2000
DOI: 10.1029/1999jb900358
|View full text |Cite
|
Sign up to set email alerts
|

Rock magnetic properties related to thermal treatment of siderite: Behavior and interpretation

Abstract: Abstract. Detailed analyses of rock magnetic experiments were conducted on the oxidation products of high-purity natural crystalline siderite that were thermally treated in air atmosphere. Susceptibilities increase sharply between 400 ø and 530øC indicative of some new ferrimagnetic mineral phase generation. Both a drop (between 540 ø and 590øC) on the heating cycle and a dramatic increase (from 590øC to 520øC) on the cooling cycle occurred and are well consistent with the characteristic of magnetite. A distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 30 publications
4
79
0
1
Order By: Relevance
“…3j, m, p), which indicates the dominance of (titano-)magnetite as the main magnetic carrier. The peak or hump at around 450-500°C may result from the neo-formation of magnetite grains from iron-containing minerals silicates, clays or carbonates (Deng et al, 2001;Zhang et al, 2014;Pan et al, 2000). This is consistent with significant increases of magnetic susceptibility in the cooling curves compared with their heating counterparts (insets in Fig.…”
Section: χ-T and Sirm 20 K_25 T -T Resultssupporting
confidence: 72%
“…3j, m, p), which indicates the dominance of (titano-)magnetite as the main magnetic carrier. The peak or hump at around 450-500°C may result from the neo-formation of magnetite grains from iron-containing minerals silicates, clays or carbonates (Deng et al, 2001;Zhang et al, 2014;Pan et al, 2000). This is consistent with significant increases of magnetic susceptibility in the cooling curves compared with their heating counterparts (insets in Fig.…”
Section: χ-T and Sirm 20 K_25 T -T Resultssupporting
confidence: 72%
“…The magnetic susceptibility increases moderately from room temperature to~300°C, which is likely due to the gradual unblocking of fine-grained (near the superparamagnetic/single-domain (SP/SD) boundary) ferrimagnetic particles . The abrupt increase of magnetic susceptibility above~400°C with a hump at 500°C followed by a quick decrease to zero may reflect the existence of siderite (Pan et al, 2000). T c of~580°C demonstrates the presence of magnetite.…”
Section: Demagnetization Of the Natural Remanent Magnetization (Nrm)mentioning
confidence: 99%
“…In addition, Hirono et al (2006bHirono et al ( , 2007 reported high magnetic susceptibilities in the black gouge within each of the major fault zones, and proposed two possible explanations: (1) ferrimagnetic grains were crushed into submicrometer size by shearing, while the total concentration of magnetic mineral did not change or (2) magnetite or maghemite grains were newly formed by thermal decomposition of paramagnetic phases such as siderite (Pan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%